An impedance based microfluidic biosensor for white blood cell counting - Lim, Cheryl Shu Ching (2019)
In the process of collection of biological samples for testing, the issue of insufficient samples has been a perennial issue for a variety of reasons, whether due to unsuitability caused by improper storage conditions or the difficulty in re-collection of fluids such as cerebrospinal fluid. Currently, biological samples need to be sent to laboratories for lengthy and costly processing, with the use of dyes and other staining methods applied for cell identification accounting for a significant portion of testing costs.